Current transformer reaction with linear and non-linear loads - Ismail, Daut, Prof. Dr.; Khairul Anuar, Mohd Nor; Indra, Nisja; Shatri, C.; Reza, Mohyin (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/